Parental perceptions of prenatal whole exome sequencing (PPPWES) study. (5th August 2018) - Wou, Karen; Weitz, Talia; McCormack, Clare; Wynn, Julia; Spiegel, Erica; Giordano, Jessica; Wapner, Ronald J.; Chung, Wendy K.
Abstract: Objective: The objective of the study is to investigate the experiences of couples who underwent prenatal whole‐exome sequencing (WES) for fetal anomalies and the amount/type of information couples want from prenatal WES. Method: Participants in the Fetal Sequencing Study who had genetic testing for fetal anomalies were invited for a semistructured interview about their experience with prenatal WES. A constructivist grounded theory approach with an inductive coding style was used for coding and analysis. Results: We interviewed 29 participants from 17 pregnancies. Two pregnancies had positive prenatal WES results, and 4 were terminated prior to receipt of WES results. The main themes were anxiety and stress around the time of diagnosis, education and consent for WES, coping and support while waiting for results, and receiving genetic testing results. In response to hypothetical scenarios probing the desire for uncertain results, 86% would like to be told about results for which the provider had some degree of uncertainty, and the percent desiring results decreased as the certainty of the results decreased. Conclusion: Participants' experience with exome sequence was similar to other prenatal genetic diagnostic tests, except for the longer wait time for results. When probed with hypothetical scenarios, participants desired more results than were provided in the study, including uncertain results that might diagnose the fetal condition. This highlights the need for specialized prenatal genetic counseling to have nuanced discussions of multiple dimensions of uncertainty with implementation of prenatal WES. Abstract : What's already known about this topic? Prenatal whole‐exome sequencing (WES) has been introduced clinically on a small scale based upon the postnatal WES experience with the potential to provide definitive diagnoses prenatally. What does this study add? Our study adds the patient perspective to understand their experiences and the utility of prenatal WES. Their experience showed no real difference when compared to prenatal chromosome microarrays except for a longer wait period for results and the amount/type of information desired from prenatal WES when presented with hypothetical scenarios of returning various results.